2011
DOI: 10.1016/j.jval.2011.02.656
|View full text |Cite
|
Sign up to set email alerts
|

Pin25 Cost-Effectiveness Analysis of the Introduction of the Varicella Vaccine in Colombia

Abstract: the model is robust to a wide range of parameter estimates. CONCLUSIONS: This analysis suggests that the use of ATVϩRTV in the Mexican healthcare setting is a preferred option when compared to LPVϩRTV for treatment of treatment-naïve HIV patients. OBJECTIVES:To examine the incremental cost-effectiveness of palivizumab vs. no prophylaxis among 3 groups of preterm infants in a Medicaid population. Infants were Յ6 months of age at the start of the RSV season: 1) Յ32 weeks gestational age (wGA); 2) High-risk (HR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Three studies provided economic evaluations of vaccination prior to the introduction of universal vaccination programs in Colombia [64, 65] and Brazil [63]. All three studies utilized a decision analysis model, but each study was conducted with a different perspective: societal [63], payer [65], or provider [64]. The time horizon was 30 years in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies provided economic evaluations of vaccination prior to the introduction of universal vaccination programs in Colombia [64, 65] and Brazil [63]. All three studies utilized a decision analysis model, but each study was conducted with a different perspective: societal [63], payer [65], or provider [64]. The time horizon was 30 years in all studies.…”
Section: Resultsmentioning
confidence: 99%
“…In a second study in the Colombian setting, De La Hoz et al [65] concluded that the varicella cost with vaccination was lower than the varicella cost without vaccination (US $35 million vs. US $88 million in 2008 [equivalent to US $40.6 million vs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, having compared incremental cost per QALY results with a local threshold of acceptable cost per QALY, reported whether the threshold had been satisfied or not [ 51 , 53 , 56 , 58 , 59 , 61 , 64 , 68 , 87 ]. Yet others reported whether there was a dominant option in the sense of having a higher level of QALYs and lower cost than a comparator [ 16 , 53 , 54 , 57 , 59 , 62 , 65 , 81 , 83 , 84 , 88 ]. There were examples of disparate findings emerging from studies which apparently have much in common [ 59 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is uncertain whether vaccination costs were included in these studies. Four studies reported incremental cost per life year gained or incremental cost per death prevented, but not incremental cost per QALY gained or a benefit-cost ratio [ 65 , 70 , 77 , 102 , 103 ]. Since death, though not unknown, is uncommon in varicella, we would expect these costs to be high.…”
Section: Resultsmentioning
confidence: 99%